The Graphic : an illustrated Weekly Newspaper (voortgezet als: The National Graphic (1932)) - Thomas, William Luson; Thomas, Lewis Samuel (Londen : William Luson Thomas Company, 1869)
The Graphic was a British weekly illustrated newspaper, first published on 4 December 1869 by William Luson Thomas's company Illustrated Newspapers Ltd. Thomas's brother Lewis Samuel Thomas was a co-founder. The influence of The Graphic within the art world was immense, its many admirers included Vincent van Gogh. It continued to be published weekly under this title until 23 April 1932 and then changed title to The National Graphic between 28 April and 14 July 1932; it then ceased publication, after 3,266 issues. From 1890 until 1926, Luson Thomas's company, H. R. Baines & Co., published The Daily Graphic. (Wikipedia)
Https://en.wikipedia.org/wiki/The_Graphic
Https://www.newspapers.com/paper/the-graphic-an-illustrated-weekly-newspaper/7833/ (gelimiteerd)
Online: https://archive.org/details/nationalgraphic en https://catalog.hathitrust.org/Record/000533840 (enkele nummers)
Engels
Krant, nieuwsbulletin